International Criminal Law and International Crimes - Sántha, Ferenc; Bartkó, Róbert (Criminal Legal Studies: European Challenges and Central European Responses in the Criminal Science of the 21st Century, 2022)
This paper outlines the underlying concepts, statutory elements, and characteristics of the socalled core international crimes (genocide, crimes against humanity, war crimes, and the crime of aggression) and terrorist crimes. The core international crimes, the act of terrorism, and criminal offenses regarding terrorism are subject to international criminal law. Libraries could be filled with literature on the concept of international criminal law; however, it suffices to refer to the fact that international criminal law is a relatively young area of law that emerged at the boundaries of public international and domestic law. International criminal law cannot be considered a separate branch of law but rather a body of law created by the functional interaction of several branches or areas of law (international, criminal, and constitutional law). This study employs the comparative perspective to address the statutory definitions of the noted crimes and examines the legal way to implement the international requirements by the relevant national laws.KEYWORDS: international core crimes, terrorism, international criminal law, criminal offenses related to terrorism, European criminal law